Microdroplet and spatter contamination during phacoemulsification cataract surgery in the era of COVID‐19. (11th October 2020) - McGhee, Charles N. J.; Dean, Simon; Freundlich, Simone E. N.; Gokul, Akilesh; Ziaei, Mohammed; Patel, Dipika V.; Niederer, Rachael L.; Danesh‐Meyer, Helen V.
Abstract: Importance: Determine phacoemulsification cataract surgery risk in a Covid‐19 era. Background: SARS‐CoV‐2 (Covid‐19) transmission via microdroplet and aerosol‐generating procedures presents risk to medical professionals. As the most common elective surgical procedure performed globally; determining contamination risk from phacoemulsification cataract surgery may guide personal protection equipment use. Design: Pilot study involving phacoemulsification cataract surgery on enucleated porcine eyes by experienced ophthalmologists in an ophthalmic operating theatre. Participants: Two ophthalmic surgical teams. Methods: Standardized phacoemulsification of porcine eyes by two ophthalmologists accompanied by an assistant. Fluorescein incorporated into phacoemulsification irrigation fluid identifying microdroplets and spatter. Contamination documented using a single‐lens reflex camera with a 532 nm narrow bandpass (fluorescein) filter, in‐conjunction with a wide‐field blue light and flat horizontal laser beam (wavelength 532 nm). Quantitative image analysis using Image‐J software. Main Outcome Measures: Microdroplet and spatter contamination from cataract phacoemulsification. Results: With phacoemulsification instruments fully within the eye, spatter contamination was limited to <10 cm. Insertion and removal of the phacoemulsification needle and bimanual irrigation/aspiration, with irrigation active generated spatter on the surgeons' gloves and gown extending to >16 cm below the neckline in surgeon 1 and > 5.5 cm below the neckline of surgeon 2. A small tear in the phacoemulsification irrigation sleeve, presented a worse‐case scenario the greatest spatter. No contamination above the surgeons' neckline nor contamination of assistant occurred. Conclusions and Relevance: Cataract phacoemulsification generates microdroplets and spatter. Until further studies on SARS‐CoV‐2 transmission via microdroplets or aerosolisation of ocular fluid are reported, this pilot study only supports standard personal protective equipment.